2018
DOI: 10.1007/s00394-018-1726-x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate consumption of a soluble green/roasted coffee rich in caffeoylquinic acids reduces cardiovascular risk markers: results from a randomized, cross-over, controlled trial in healthy and hypercholesterolemic subjects

Abstract: Regular consumption of moderate amounts of a soluble green/roasted (35:65) coffee blend may contribute to improve cardiovascular health in moderately hypercholesterolemic people, as reducing serum lipids, blood pressure and body weight effects, as well as increasing plasma antioxidant capacity, have been observed. Moreover, positive influences on blood pressure, body weight, and plasma antioxidant capacity were obtained in the healthy group. Therefore, incorporation of green coffee beans into the coffee brew c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 61 publications
5
89
2
3
Order By: Relevance
“…Phenolic acid intake was associated only with higher antiinflammatory IL-4. As coffee was the main food contributor of phenolic acids in the HELENA study (12), this corroborates previous findings: IL-4 was positively associated with coffee consumption in rats (43) and tended to be increased by moderate soluble green/roasted (35:65) coffee intake in hypercholesterolemic adults (44).…”
Section: Inflammation and Polyphenol Classessupporting
confidence: 89%
“…Phenolic acid intake was associated only with higher antiinflammatory IL-4. As coffee was the main food contributor of phenolic acids in the HELENA study (12), this corroborates previous findings: IL-4 was positively associated with coffee consumption in rats (43) and tended to be increased by moderate soluble green/roasted (35:65) coffee intake in hypercholesterolemic adults (44).…”
Section: Inflammation and Polyphenol Classessupporting
confidence: 89%
“…In subjects with hypercholesterolemia, daily consumption of a green/roasted coffee blend for 8 weeks increased the levels of total, LDL, and VLDL cholesterol and triglycerides. [ 80 ] Such an effect was not seen in subjects with normal cholesterol levels.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 24 studies were related to cancer ( Table 1 ), [ 17–40 ] and 50 studies to cardiometabolic diseases ( Table 2 ). [ 41–90 ]…”
Section: Methodsmentioning
confidence: 99%
“…In another RCT study by Gavrieli et al, coffee delayed the postprandial glucose response more in females and overweight or obese participants compared to men and participants with normal weight, respectively [127]. A randomized crossover study, where coffee containing green and roasted beans was consumed by 52 volunteers, found decreased levels of lipid markers (LDL-C, VLDL-C, and triglycerides) only in the hypercholesterolemic group (n = 27), but not in the normocholesterolemic one (n = 25) [128]. The same research group also found a decrease in some markers of metabolic syndrome (blood glucose, insulin resistance, and triglycerides) after consumption of green/roasted coffee blend only in hypercholesterolemic subjects [129].…”
Section: Interindividual Variability In Health Responsesmentioning
confidence: 99%